Development of Android-Based Sikair Interactive Learning Media to Improve Students' Learning Outcomes in The Water Cycle - Widya Septiani; Budi Hendrawan; Rahmat Permana (CV. Ksatria Siliwangi, 2023)
This study aims to develop a product in the form of interactive learning media based on Android to improve student learning outcomes in elementary schools. This study uses the Research and Development method. This research was conducted at SDN 2 Courts. The results of the validation of the Android-based interactive interactive media were carried out by experts such as material experts, media experts and linguists. Each expert is as follows: the material expert gives a final score of 1 with the eligibility criterion of 100% or can be said to be